Bireyin Söylem Kalitesinin Toplumsal Yaşama Yansımaları Kavramsal Bir Bakış - Zeybek, Işıl (YAÜ Sosyal Bilimler Enstitüsü, 2013)
The lives of individuals have been affected both positively and negatively by the rapidly growing technological environment. Despite the fact that technological novelties render communication effortless, it also prevents socialization, masking alienations and loneliness with ‘sharing’. This alienation and loneliness brings about certain problems to the surface, such as the incapability of individuals to express themselves in a coherent manner. In this context, this study will question the discourses of interpersonal relationships in communal living.
Keywords: Kişilerarası İletişim; Kalite; Söylem; İletişim Becerileri